Appropriation as a condition for the right to the city. The case of the neighbourhood improvement policy of Villa Jardín, Municipality of Lanús, Buenos Aires - Jaime, Eugenia (2023)
During the last twenty years, public policies for neighborhood improvement have been developed in the region with the purpose of urbanizing precarious settlements. However, these interventions have affected a relevant mass of inhabitants to fully develop their right to the city. On the other hand, the obstacles that faced the settlers to transit these processes in an appropriate manner are significant, according to Lefebvre's terms, as a condition for a just and democratic production.This article reflects, based on the work of the civil association Proyecto Habitar, in alliance with the Defensoría General de la Nación Argentina during 2018, on the role played by appropriation in urbanization processes that include population relocation, specifically the implementation of a public policy of neighborhood improvement in Villa Jardín - Lanús in Metropolitan Area of Buenos Aires. For the analysis, three dimensions were established: technical-constructive aspects, the socio-organizational aspect and, finally, the political and institutional aspects. This multidimensional approach seeks to identify the role of ownership in achieving and realizing the right to the city.